Evaluation of the antioxidant, anti-inflammatory, and anti-tumoral properties of bioactive compounds extracted from murta berries (Ugni molinae T.) dried by different methods - López, Jéssica; Vega-Gálvez, Antonio; Ah-Hen, Kong S.; Rodríguez, Angela; Quispe-Fuentes, Issis; Delporte, Carla; Valenzuela-Barra, Gabriela; Arancibia, Yennyfer; Zambrano, Angara (Frontiers in Plant Science, 2023)
This study evaluated the effects of different drying methods (freeze drying, vacuum drying, infrared drying, convective drying, and sun drying) on the biological properties of berries from the Chilean murta (Ugni molinae Turcz) shrub. Physical-chemical properties (proximal composition, dietary fiber, sugars) were determined. Total phenolic content through the method of Folin-Ciocalteau, the profile of phenol compounds was determined by HPLC, and antioxidant potential by DPPH and ORAC assays were also evaluated. The topic anti-inflammatory effect was evaluated by mice´s ear edema, and in vitro anti-tumoral activity was tested by MTT assay. The chemical properties of dried berries differed significantly based on the drying method: freeze-dried murta berries showed increased total phenolic content extracted over fresh and dried samples. In addition, this lyophilized extract stood out in its antioxidant potential, in both assays evaluated (DPPH and ORAC), compared to the other drying methods. Notwithstanding, vacuum- and infrared-dried murta also showed a higher ORAC value. Antioxidant potential was significantly associated with phenolic compounds catechin and pyrogallol, which were the most abundant phenolic compounds present in all samples. The anti-inflammatory activity was most effective under freeze-drying and vacuumdrying conditions. Moreover, vacuum drying and infrared drying best preserved the anti-tumoral effect on cancer cells.